2013
DOI: 10.1177/0363546513508261
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Revision Meniscal Repair

Abstract: Revision meniscal repair should be considered in the setting of a retorn meniscus without degenerative changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…A second major limitation was the lack of subgroup analysis to evaluate for differences that may have been present among patient tear types, ages, or demographics. Several studies have suggested that complex or challenging tears are less likely to heal reliably [6,13,27]. In this setting, although PRP may have enhanced the biology of the repaired meniscus, failure resulting from tear characteristics may have been inevitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second major limitation was the lack of subgroup analysis to evaluate for differences that may have been present among patient tear types, ages, or demographics. Several studies have suggested that complex or challenging tears are less likely to heal reliably [6,13,27]. In this setting, although PRP may have enhanced the biology of the repaired meniscus, failure resulting from tear characteristics may have been inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings have led to a renewed focus on meniscal preservation strategies to prevent articular cartilage degeneration. Recent efforts have been directed toward repair or enhancement rather than resection of the injured meniscus [6,11,13,17,[20][21][22]26]; however, even with the best techniques, meniscus repairs can fail. Newer options for meniscus transplantation and tissue engineering have shown some promise, but current evidence regarding long-term outcomes compared with meniscus repair is lacking [5,26].…”
Section: Introductionmentioning
confidence: 99%
“…121 The healing status of repaired menisci can be assessed with various outcomes measures, including patient pain/function, imaging, and second-look arthroscopy (Fig. 19).…”
Section: Repair Outcomesmentioning
confidence: 99%
“…Until now, meniscectomy seems to be the preferred technique to address failed meniscus repairs [1417]. However, revision meniscal repair may provide better long-term outcomes than meniscectomy, but the results of this procedure remain underreported [18–21]. It is therefore unclear if revision meniscal repair is worthwhile.…”
Section: Introductionmentioning
confidence: 99%